Greater Mitochondrial Energy Production Provides Resistance to Ocean Acidification in “Winning” Hermatypic Corals - Agostini, Sylvain; Houlbrèque, Fanny; Biscéré, Tom; Harvey, Ben P.; Heitzman, Joshua M.; Takimoto, Risa; Yamazaki, Wataru; Milazzo, Marco; Rodolfo-Metalpa, Riccardo (Frontiers in Marine Science, 2021)
Coral communities around the world are projected to be negatively affected by ocean acidification. Not all coral species will respond in the same manner to rising CO2 levels. Evidence from naturally acidified areas such as CO2 seeps have shown that although a few species are resistant to elevated CO2, most lack sufficient resistance resulting in their decline. This has led to the simple grouping of coral species into ‘winners’ and ‘losers’, but the physiological traits supporting this ecological assessment are yet to be fully understood. Here using CO2 seeps, in two biogeographically distinct regions, we investigated whether physiological traits related to energy production (mitochondrial electron transport systems activities) and biomass (protein contents) differed between winning and losing species in order to identify possible physiological traits of resistance to ocean acidification and whether they can be acquired during short-term transplantations. We show that winning species had a lower biomass (protein contents per coral surface area) resulting in a higher potential for energy production (biomass specific ETSA: ETSA per protein contents) compared to losing species. We hypothesize that winning species inherently allocate more energy towards inorganic growth (calcification) compared to somatic (tissue) growth. In contrast, we found that losing species that show a higher biomass under reference pCO2 experienced a loss in biomass and variable response in area-specific ETSA that did not translate on an increase in biomass-specific ETSA following either short-term (four to five months) or even life-long acclimation to elevated pCO2 conditions. Our results suggest that resistance to ocean acidification in corals may not be acquired within a single generation or through the selection of physiologically resistant individuals. This reinforces current evidences suggesting that ocean acidification will reshape coral communities around the world, selecting species that have an inherent resistance to elevated pCO2.